A REVIEW OF THE SPATIAL AND TEMPORAL VARIATIONS IN THE VEGETATIVE AND REPRODUCTIVE DEVELOPMENT OF Sargassum C. AGARDH (FUCALES, PHAEOPHYCEAE) - Veloso, Ana Paula A. (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2009)
The Sargassum C. Agardh (Fucales, Phaeophyceae) genus is composed by species of recognized ecological importance to coastal ecosystems, especially to rocky shore communities of tropical and warm temperate zones. Some species are considered valuable for presenting substances of potential biotechnological uses. However, the biological parameters of growth and reproduction of the species are insufficiently known, like the determinant factors causing variations within and among the different populations. The present study summarizes what is known about temporal and spatial variations in the vegetative and reproductive development of Sargassum species, based on the scientific literature.